2017
DOI: 10.1186/s12906-017-1685-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced efficacy with reduced toxicity of chemotherapy drug 5-fluorouracil by synergistic treatment with Abnormal Savda Munziq from Uyghur medicine

Abstract: BackgroundAbnormal Savda Munziq (ASMq) is a traditional prescription in Uyghur Medicine, and its treatment of complex diseases such as tumors and asthma has been proven to be effective in Uyghur medical clinical practice. The efficacy-enhancing and toxicity-reducing properties of ASMq were studied on mice with transplanted cervical cancer (U27) tumors, which were treated with 5-fluorouracil (5-FU) in this work.MethodsTo investigate the synergistic effect of ASMq and 5-FU on U27 cells, inhibitory effects on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In previous animal experimental models, 5-FU signi cantly affect weight of spleen, kidney and to lesser extent liver (Gelen et al 2018;Whittaker et al 2016;Yang et al 2017). In the current experiment, visceral organs weight assessment indicated that 5-FU decline splenic weight about 66% and kidney weight about 32%, as compared to the normal control (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In previous animal experimental models, 5-FU signi cantly affect weight of spleen, kidney and to lesser extent liver (Gelen et al 2018;Whittaker et al 2016;Yang et al 2017). In the current experiment, visceral organs weight assessment indicated that 5-FU decline splenic weight about 66% and kidney weight about 32%, as compared to the normal control (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In previous animal experimental models, 5-FU signi cantly affect weight of spleen, kidney and to lesser extent liver (Gelen et al 2018;Whittaker et al 2016;Yang et al 2017). In the current experiment, visceral organs weight assessment indicated that 5-FU decline splenic weight about 66% and kidney weight about 32%, as compared to the normal control (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…After overnight incubation in a CO 2 incubator at 37 °C, cells were treated with a 2-fold serial range of concentrations of MSG (100–0.78 μg/ml) followed by incubation for 24, 48, and 72 h. After that, MTT (5 mg/ml) was added to each well and re-incubated for 4 h. Formazan crystals were dissolved in DMSO, and optical density was recorded using a microplate reader at 570 nm. The cell viability percentage was estimated in comparison to the control [ 51 ]. The assay was carried out in triplicates measurement and at least three independent experiments.…”
Section: Methodsmentioning
confidence: 99%